Rainfall and river flow trends using Mann–Kendall and Sen’s slope estimator statistical tests in the Cobres River basin - Marques da Silva, Richarde (2015)
The main objective of this study is to obtain a better understanding of the spatial and temporal variability and trends of rainfall and river flow in the Cobres River basin, southern Portugal, using statistical tools. The present study is focused on the analysis of the trends in annual precipitations and river flow at a regional scale over 40 years (1960–2000). Datasets of daily precipitation recorded in eight rainfall stations and three river flow stations were analyzed. The nonparametric Mann–Kendall and Sen’s methods were used to determine whether there was a positive or negative trend in rainfall data with their statistical significance. A detailed statistical analysis applied to the river flow and rainfall time series of all gauges indicates that rainfall is highly temporally variable and there is a decrease in the annual rainfall amount for the period studied (1960–2000). Thus, there are signs of significant rainfall reduction in the basin, and in fact, some rain gauges show a small rainfall increase during the recent decades. The annual river flow variation has a cyclic behavior with a period length of approximately 10 years. The results seem integrated to the global and European continental scale findings: Decreasing trends are dominant for almost all indices; most of the calculated slopes are statistically insignificant; the distribution of positive and negative slopes in the area is extremely irregular; and the changes in basin are more significant compared to other studies.